The Power of Narrative in Environmental Networks - Raul Lejano, Mrill Ingram, and Helen Ingram (The MIT Press, 2013)
This book is a product of an extended conversation between a geographer and two policy scholars. We all share an interest in networks and relationality because these ideas help analyze environmental governance. Our individual scholarship has revolved around the opening up of the complex combinations of personal, community, and public forces and structures that inform the decisions people make, or try to make, about the environment. We were all attracted by the power of networks to describe this complexity but also interested in developing analytical tools sensitive to the heterogeneity of networks of environmental governance that we were all studying. How could we grasp some of this diversity in a way that helps explain innovation, or lack of it, regarding environmental governance? We all saw potential in the power of story and in tools offered by literary theory and analysis to capture the diversity of personal and public, affective and institutional dimensions. We sought a way to describe narratives not as good, just, hapless, and ineffective, but instead as reflecting the concerns, hesitations, and ambitions of people as they react to, shape, and are shaped by their environment. Coming from different disciplinary backgrounds, and informed by different literature, it took time (over two years) to create a common framework and to develop an analytic that appeared robust and useful to all of us. In working toward this goal, we were enabled by many other people and have benefited greatly from their advice and input. Early inspiration stemmed in part from the participation of one author (Mrill Ingram) in a faculty seminar at the University of Wisconsin-Madison on narratives, networks, and the HBO series The Wire . The motivation behind the seminar, held in the fall of 2009, came from a collaboration between UW sociology professor Lew Friedland, who has worked extensively with networks, and Caroline Levine, professor of English, an authority on narrative.